2015
DOI: 10.1590/s1517-838246220130963
|View full text |Cite
|
Sign up to set email alerts
|

Psychrotrophic bacteria in milk: How much do we really know?

Abstract: The occurrence of psychrotrophic bacteria in raw milk is studied worldwide due to the difficulties associated with controlling their growth during cold storage and the consequent negative effects upon fluid milk or dairy products. Among the psychrotrophic bacteria, the genus Pseudomonas (represented primarily by P. fluorescens) has been highlighted as the cause of numerous defects in dairy products. In light of its perceived predominance, this species has frequently been chosen as a model organism to assess th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
62
0
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 116 publications
(84 citation statements)
references
References 61 publications
2
62
0
9
Order By: Relevance
“…Milk freshly drawn from the udder often does not contain detectable populations of psychrotrophic bacteria [25]. However, after milk collection psychrotrophic bacteria grow also when the cold chain is applied.…”
Section: Psychrotrophic Microorganismsmentioning
confidence: 99%
See 2 more Smart Citations
“…Milk freshly drawn from the udder often does not contain detectable populations of psychrotrophic bacteria [25]. However, after milk collection psychrotrophic bacteria grow also when the cold chain is applied.…”
Section: Psychrotrophic Microorganismsmentioning
confidence: 99%
“…However, after milk collection psychrotrophic bacteria grow also when the cold chain is applied. Despite these microorganisms have optimal and maximal growth temperatures above 15 and 20 • C, respectively [25], they have, in fact, the ability to grow at low temperatures, such as 2-7 • C. This means that over time psychrotrophic populations can develop in cold stored raw milk and their presence in the raw milk microbiota can become a matter of concern. The drawback of psychrotroph presence in milk is their ability to produce extracellular enzymes, mainly proteases and lipases, which are responsible for spoiling milk but also dairy products, as the extracellular enzymes can resist pasteurization and even ultra-high temperature processing [26].…”
Section: Psychrotrophic Microorganismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have reported the prevalence of pathogenic Psychrotrophic in ice cream. 1,[6][7][8][9][10][11][12] Despite the effective removal of Staphylococcus aureus via pasteurization in milk, its low infective dose and ability to survive unfavourable environments make this bacterium a serious risk to consumers. 10,13,14 Ice cream can be contaminated with Staphylococcus aureus by the introduction of flavourings and ingredients (nut and chocolate) during ice cream production or from the nasal cavities and hands of carriers during food production.…”
Section: Introductionmentioning
confidence: 99%
“…This organism infects approximately one-third of all burn wounds 19 . Additionally, Pseudomonas aeruginosa has negative industrial and environmental influences, causing dairy spoilage 20 and issues in water treatment systems 21 . Therefore, applying electric potential could be a complementary approach in addition to using chemical-based drugs to overcome the issue of multi-drug resistance.…”
Section: Introductionmentioning
confidence: 99%